2013
DOI: 10.1074/jbc.m112.422527
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Changes in Histone Modifications, mRNA Levels, and Metabolite Profiles in Clonal INS-1 832/13 β-Cells Accompany Functional Adaptations to Lipotoxicity

Abstract: Background: Epigenetic regulation may mediate lipotoxic effects on ␤-cells in type 2 diabetes. Results: Lipotoxicity impairs insulin secretion, and alters metabolism, gene expression, and histone marks in INS-1 832/13 ␤-cells. Conclusion: Perturbed insulin secretion results from epigenetic, genetic, and metabolic adaptations to increased fatty acid metabolism in ␤-cells. Significance: Elucidation of the link between lipotoxicity and insulin secretion is crucial for understanding the pathogenesis of type 2 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
66
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 79 publications
(75 reference statements)
10
66
1
Order By: Relevance
“…In low glucose, INS-1 832/13 cells oxidized labeled palmitate to CO 2 at rates of 0.2-0.4 nmol·min Ϫ1 ·mg protein Ϫ1 (279,332,407). These rates are comparable to those for the utilization of 2.8 mM glucose by these cells (332).…”
Section: E Fatty Acidssupporting
confidence: 52%
See 4 more Smart Citations
“…In low glucose, INS-1 832/13 cells oxidized labeled palmitate to CO 2 at rates of 0.2-0.4 nmol·min Ϫ1 ·mg protein Ϫ1 (279,332,407). These rates are comparable to those for the utilization of 2.8 mM glucose by these cells (332).…”
Section: E Fatty Acidssupporting
confidence: 52%
“…While the authors found a fivefold increase in glutamate within 30 min in INS-1E cells and human islets, other workers (49,314) found no correlation between islet glutamate levels and insulin secretion with a variety of secretagogues, while metabolite profiling of INS-1 832/13 cells showed no significant change in whole cell glutamate levels between low and high glucose (332). The reason for these discrepancies is unclear.…”
Section: Glutamate As a Candidate Coupling Factormentioning
confidence: 46%
See 3 more Smart Citations